Off-Center Rotational Dynamics in Virtual Reality: Effects on Cybersickness and Presence - Sion Cha; Jonghyeon Ka; Imbo Kong; Junseok Ma; Sangyeon Park; Wooksung Kim (IEEE Access, 2025)
This study investigates the effects of off-center rotational acceleration and rotational radius on cybersickness and spatial presence in virtual reality (VR) environments through a set of constrained rotational scenarios. Unlike previous studies, which assumed that the rotational axis is aligned with the virtual user position, this research focuses on off-center rotations, which more frequently occur in VR without alignment to the user position. Rotational acceleration significantly increased cybersickness severity, while its effect on presence was less substantial. As rotational radius increased, both cybersickness and presence intensified, with the influence on presence being more pronounced. Multiple regression analysis (MRA) revealed that, like acceleration, radius is a significant factor influencing cybersickness and presence. Additionally, individual linear regression analysis (LRA) and violin plots indicated significant differences among different radius groups. The correlation between the two dependent variables was positive but weak; this result suggests that while increased presence may coincide with heightened cybersickness due to immersive factors like vection, the two variables often act independently. This suggests the need to further investigate the interplay between cybersickness and presence in VR environments.